Evaluating the Sustainable Development of Revolutionary Heritage Tourism: An Empirical Analysis of Cultural-Tourism Integration in Guangdong, China - lin, siki (Pacific International Journal, 2025)
Grounded in sustainable development theory, this study establishes a comprehensive evaluation index system to evaluate the development level of cultural-tourism integration. Employing a hybrid approach that integrates the Entropy Weight Method, TOPSIS, and a Coupling Coordination Degree Model, we conducted an empirical analysis using multi-source data from nine prefecture-level cities in Guangdong Province, China. The results reveal significant regional disparities in the development level of cultural tourism. Furthermore, we identify an inverse relationship between economic efficiency and ecological carrying capacity in most of the sampled cities. A widespread imbalance is also observed, characterized by a high degree of coupling yet a low degree of coordination among the economic, social, environmental, and cultural subsystems. The findings offered theoretical insights and practical implications for promoting the high-quality and sustainable development of cultural tourism.